Modern problems and peculiarities of the resettlement policy of the Russian Federation - E. F. Aydynbekov (Статистика и экономика, 2017)
For the effective management of migration processes, maximizing the positive outcomes and minimizing the negative consequences, in 2012 the Russian Federation adopted the Concept of the state migration policy for the period up to 2025, which defined the main goals, objectives and principles of the Russian migration policy (hereinafter – the Concept).Stabilization and increasing permanent population of the country is one of the most important goals.However, the priority objective to achieve this goal is to create the conditions and incentives for the resettlement of compatriots, living abroad to the Russian Federation for the permanent residence, emigrants and certain categories of foreign nationals, necessary for the Russian economy.In this direction, the Concept of the state migration policy for the period up to 2025 provides as follows: [1]• Assistance to voluntary resettlement of compatriots, living abroad to the Russian Federation and emigrants’ returning;• Implementation of the State program to assist the voluntary resettlement of compatriots, living abroad to the Russian Federation, its modernization and making it termless;• Facilitating resettlement of foreign nationals for the purpose of family reunification to the Russian Federation;• Upgrading of institutions of temporary residence permit and a residence permit.Taking into account the economic, demographic and political challenges and threats, assistance to the voluntary resettlement of compatriots, residing in other countries to the Russian Federation, is the most important strategic resource to solve a number of important issues and tasks.The implemented «State program to assist the voluntary resettlement of compatriots, living abroad to the Russian Federation» [2] is aimed to consolidate the potential of compatriots, to the needs of progressive development of the regions of the country and the economy as a whole.The objectives of the program are:• Promotion and organization of the voluntary resettlement of compatriots on the permanent residence in the Russian Federation;• Assistance to the social and economic development in the regions;• Solution of demographic problems, especially in the priority areas of settlement.At the same time, the State program requires a systematic improvement and adjustment, paying attention on external and internal changes.This article discusses the resettlement policy of the Russian Federation, explores the current key issues in this area, in the sphere of migration policy, analyzes the issues of improving the legal support of resettlement of compatriots, living abroad to the territory of Russia, presents statistical data on the number of participants and regional settlement, considers preferences, received by compatriots, decided to move on a permanent basis in Russia, as well as the preliminary results of the State program on resettlement of compatriots to the Russian Federation.